Long‐term outcomes of non‐alcoholic fatty liver disease and the risk factors for mortality and hepatocellular carcinoma in a Japanese population. Issue 9 (5th February 2020) - Kogiso, Tomomi; Sagawa, Takaomi; Kodama, Kazuhisa; Taniai, Makiko; Hashimoto, Etsuko; Tokushige, Katsutoshi
Abstract: Background and Aim: The incidence of mortality and hepatocellular carcinoma (HCC) in patients with non‐alcoholic fatty liver disease (NAFLD) has been reported, but the long‐term outcomes of Japanese patients with NAFLD are not fully evaluated. Methods: We enrolled 365 Japanese patients with biopsy‐confirmed NAFLD (1990–2008) followed for ≥ 6 months: 185 males (50.7%); median age (54 years); advanced fibrosis 108 (29.8%); HCC, n  = 26 (7.1%); diabetes, n  = 191 (52.3%); dyslipidemia, n  = 234 (64.1%); and hypertension, n  = 193 (52.9%). We analyzed the survival and new‐onset HCC rates for hepatic fibrosis as well as complications and the treatment of lifestyle‐related diseases. Results: During the median 7.1‐year follow‐up, 44 patients (12.1%) died: n  = 28 liver‐related (10 years liver‐related death, 9.4%) and n  = 16 non‐liver‐related deaths (10 years non‐liver‐related death, 4.9%). Both incidence rates were significantly higher in the advanced fibrosis group. The incidence of HCC at 10 years was 20.1% in the advanced fibrosis group, and the mortality was increased in patients with higher age, history of HCC, lower seru\m level of albumin, higher level of γ‐glutamyltransferase, and insulin treatment for diabetes. Risk factors for HCC onset were higher levels of aspartate aminotransferase and triglyceride and hypertension treatment. Platelet count < 11.5 × 10 4 /μL was revealed as a risk factor for death and HCC development. Conclusions: The rates of both liver‐related and non‐liver‐related deaths and HCC development were significantly prominent in the patients with advanced fibrosis. It is important to identify and treat NAFLD patients who have several risk factors and advanced fibrosis, which might be predicable simply by the platelet count.